Pengaruh Kepemimpinan, Struktur Organisasi dan Budaya Organisasi terhadap Kinerja Dinas serta Implikasinya pada Pelayanan Publik - Dedi Hadian (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2015)
The purpose of this study was to analyze the influence leadership, organizational structure, organizational culture and performance and public services, and the influence of leadership, organizational structure, organizational culture, also the effect of performance on public services. The method used is descriptive and verification with simple technique by using proportional random sampling on 350 respondent. The data was analyzed using Path analysis techniques (Path Analysis). The results indicate that: leadership was pretty good, organizational structure was good enough, organizational culture was quite good, performance was well enough, public services good enough either there was different significan either partially or simultaneously from the variable of leadership, organizational structure, organizational culture and performance, there was a strong influence of performance on public services.